2004
DOI: 10.1021/jp0311355
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Memory on Transition between the B2 and B4 Phases in an Achiral Banana-Shaped Molecular System

Abstract: The correlation between chirality of the B2 and B4 phases was examined by measuring the circular dichroism (CD) in the classic bent-core molecule, P-12-O-PIMB, which shows a direct B2 to B4 phase transition on cooling. Among the various structures formed in the tilted B2 phase, the homochiral SmC S P F and SmC A P A layer structures show a distinct CD peak at around 400 nm, while no CD effect is observed in the racemic SmC S P A layer structure. In contrast, the lower temperature smectic B4 phase is essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 19 publications
6
86
1
1
Order By: Relevance
“…During this process a simultaneous reversal in the polarization and the tilt direction takes place giving rise to a switching from SmC s P A to SmC a P S and SmC a P A to SmC s P S . Bent-core mesogens are well known for the optically isotropic phases they exhibit, which include the B4 phase [7][8][9], the dark conglomerate (DC) [10][11][12][13][14][15][16][17][18][19] and the dark enantiomeric (DE) phases [20]. The DC phase, which is the topic of interest of this paper, is usually found to occur below the isotropic phase.…”
Section: Introductionmentioning
confidence: 99%
“…During this process a simultaneous reversal in the polarization and the tilt direction takes place giving rise to a switching from SmC s P A to SmC a P S and SmC a P A to SmC s P S . Bent-core mesogens are well known for the optically isotropic phases they exhibit, which include the B4 phase [7][8][9], the dark conglomerate (DC) [10][11][12][13][14][15][16][17][18][19] and the dark enantiomeric (DE) phases [20]. The DC phase, which is the topic of interest of this paper, is usually found to occur below the isotropic phase.…”
Section: Introductionmentioning
confidence: 99%
“…One such set of phases exhibited by bent-core liquid crystals (BCLCs) are optically isotropic, including the recently discovered B4 and the dark conglomerate (DC) phases. The discovery of these phases and the subsequent understanding of their internal structures are two of the major developments in the field of BCLCs [4][5][6][7][8][9][10][11][12][13][14][15][16]. A characteristic common to the DC and the B4 phases is spontaneous breaking of chiral symmetry that occurs even though the constituent molecules are achiral.…”
Section: Introductionmentioning
confidence: 99%
“…Freeze-fracture transmission electron microscopy (FFTEM) studies of the B4 phase revealed an assembly of twisted layers stacked to form chiral nanobundles with around wB40 nm widths and hB100 nm half pitch 6 . This helical nanofilament (HNF) phase is particularly interesting owing to its unique hierarchical nanostructure 7,8 in which the individual filaments further selforganize into oriented arrays of filaments that are phase coherent with respect to their twist. The bulk HNF phase expels most guest molecules, such as rod-shaped liquid crystals [9][10][11][12][13][14][15] , and their unique structure makes it attractive for the design of bulk and surface structures with controlled porosity and roughness at the nanometre and micrometre scales.…”
mentioning
confidence: 99%